(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Description of 24-hour preoperative dietary intake in colorectal cancer patients at Vietnam National Cancer Hospital, campus 3 in 2024. Subjects and methods: A cross-sectional descriptive study was conducted with a sample size of 126 colorectal cancer patients indicated for surgery. Results: The mean dietary energy intake was 498 ± 307,4 kcal/day. The mean intakes of protein, lipid, and carbohydrate were 20,4 ± 13,76 g/day; 13,73 ± 10,36 g/day, and 73,5 ± 45,89 g/day, respectively. Based on 24-hour dietary recall, 93,01% of patients did not meet 70% of the recommended dietary intake for energy, and 98,4% did not meet 70% of the recommended dietary intake for protein. The proportions of patients who failed to meet 70% of the recommended dietary intake for lipid and carbohydrate were 67% and 90,5%, respectively. These findings indicate that the majority of patients had inadequate dietary intake compared with the recommended dietary intake. Patients aged over 65 years were more likely to achieve ≥ 70% of the recommended dietary intake for energy compared with those aged under 65 years, and this difference was statistically significant (p = 0,03). Conclusion: The proportion of patients achieving the recommended dietary intake for energy, macronutrients, and micronutrients in the 24 hours prior to surgery was relatively low.